DEMOGRAPHIC, ECONOMIC AND PSYCHOLOGICAL DRIVERS OF WOMEN'S PARTICIPATION IN RURAL TOURISM IN DARJEELING DISTRICT, WEST BENGAL, INDIA (Journal of Event, Tourism and Hospitality Studies, 2024)
Rural tourism has gained global popularity, with varying characteristics across regions. This study explores the demographic, economic, and psychological factors influencing women's participation in rural tourism in Darjeeling, West Bengal, India. Despite its proximity to Sikkim, Darjeeling remains under-researched, particularly regarding women's motivations. Data from 200 women, including 50 in the hospitality sector, were collected via a pre-tested, interviewer-administered questionnaire to understand the push factors for their involvement. The analysis shows that middle-aged, married women with secondary or less education dominate the rural tourism workforce. Their primary motivations are economic need, improved educational opportunities for their children, and escaping socioeconomic challenges. Significant economic drivers include contributing to family businesses and achieving financial independence. Psychological factors, such as improving living conditions and securing future stability, also play a crucial role, though aspirations for leadership and decision-making are less prominent due to cultural norms. The findings highlight rural tourism's critical role in providing employment and empowerment opportunities for women in Darjeeling. Enhancing participation and empowerment requires addressing economic and psychological needs, improving income levels, supporting leadership roles, and fostering greater family decision-making power. These efforts can strengthen women's involvement in rural tourism, boosting their socioeconomic development and quality of life.